Autologous Enhancement by Interferon of Natural Killer Activity of Human Peripheral Blood Lymphocytes - S. B. Cheknev; Y. G. Ashmanova; A. D. Pritsker; O. L. Latysheva; F. I. Yershov; A. J. Kulberg (Mediators of Inflammation)
The in vitro action of interferon (IFN)-α and IFN-γ from six healthy donors and ten patients with multiple sclerosis (MS) on natural killer (INK) activity of peripheral blood lymphocytes (PBL) was studied in an autologous system. The NK activity of PBL was detected by a cytotoxic test using 3H-uridine human erythromyeloblast K562 cells. Autologous IFN-α and IFN-γ did not augment NK activity of PBL from healthy donors in vitro, whereas in samples from MS patients the IFNs strongly stimulated NK cell cytotoxic function. This stimulation suggests the existence of an inhibitor of regulatory IFN action, that is produced in healthy donors simultaneously with IFN in response to IFN induction, but which is lacking in commercial IFN preparations. The factor-containing supernatants from healthy donors reduced the stimulatory action of autologous IFNs in patients with MS almost until complete blockade. Because this inhibitor was absent in patients with MS, deficiency of an inhibitor of IFN regulatory action in MS could open the way to treatment of this compartment of the immune system.